Factors associated with nutritional status in children under five - Ari Setiawati; Darmi Arda; Nordianiwati Nordianiwati; Indrawati Aris Tyarini; Indryani Indryani (Edukasi Ilmiah Indonesia, 2023)
Nutritional status in children under five is an essential indicator of a child's health and development. Good nutrition at this age is crucial because children are experiencing rapid growth and development during this period. This study aims to determine the factors related to nutritional status in children under five—a type of quantitative research with a cross-sectional study design. The number of samples used in this study was 43 toddlers using purposive sampling techniques. The results of statistical tests obtained a value of 0.038 for maternal age, 0.405 for occupation, and 0.600 for knowledge of maternal nutrition. It can be concluded that there is no relationship between nutritional status in children under five and maternal age, occupation, or knowledge. The nutritional status of children under five is an important issue that is influenced by several factors, including the mother's age, the mother's occupation, and the mother's knowledge of child nutrition. The mother's age can affect the success of breastfeeding practices and nutritional knowledge. The mother's work plays a role in family time and resource availability. The mother's knowledge of child nutrition influences food selection and feeding practices. Handling the nutritional problems of children under five requires a holistic approach that involves all relevant parties, including the government, health institutions, and the community.